Contribution of BIM Serine 87 phosphorylation on targeted therapy response - Song, Zejia (My University, 2022)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are the standard-of-care for the treatment of EGFR-mutant non-small cell lung cancer (NSCLC) with typically excellent response rates. However, no patient can be cured due to the development of acquired drug resistance. Major contributors to drug resistance are drug tolerant persisters (DTPs) that evade apoptosis and persist under therapy. Preliminary data from the laboratory demonstrated elevated phosphorylation of pro-apoptotic protein BIM at Serine (S) 87 in DTPs, suggesting that BIM phosphorylation may play a role in apoptosis evasion upon therapy. The aim was to explore the role of BIM S87 phosphorylation in targeted therapy resistance in EGFR- mutant NSCLC. We successfully cloned wild-type BIM and BIM S87A (disrupted phosphorylation at S87), S87E (phospho-mimetic), S87D (phospho-mimetic), into doxycycline-inducible lentiviral pCW57.1 vector, and established PC-9 cells with stable, inducible expression of wild-type BIM and BIM mutants. With doxycycline dose-response assays and apoptosis assays, we demonstrated that BIM S87A is prone to apoptosis than WT BIM in PC-9 cells. Furthermore, the functional significance of BIM S87 phosphorylation was evaluated with PC-9 cells harbouring endogenous BIM S87A created using CRISPR/Cas9 technology. In long-term drug-treatment assays, cells with BIM S87A established smaller residual cell populations, consistent with enhanced BIM S87A-mediated apoptosis observed. In conclusion, the results suggest that BIM S87 phosphorylation may play a role in apoptosis evasion of DTPs. Further research is needed to identify druggable target(s) responsible for BIM S87 phosphorylation upon therapy, to prevent or delay acquired drug resistance in EGFR-mutant NSCLC patients.
Keywords: non-small cell lung cancer; BIM phosphorylation; targeted therapy tolerance, acquired drug resistance